MODERN PRINCIPLES OF THE PATHOGENESIS OF UROLITHIASIS (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2023)
Today there is no single theory describing the etiology and pathogenesis of urolithiasis. This issue remains debatable. However, it is generally accepted that there are a number of constant internal factors that may conditionally predispose to the formation of stones. The results of the analysis of literature data on the etiology and pathogenesis of urolithiasis are presented.